2017
DOI: 10.3171/2016.8.jns161226
|View full text |Cite
|
Sign up to set email alerts
|

Managing overlapping surgery: an analysis of 1018 neurosurgical and spine cases

Abstract: OBJECTIVE Overlapping surgery-the performance of parts of 2 or more surgical procedures at the same time by a single lead surgeon-has recently come under intense scrutiny, although data on the effects of overlapping procedures on patient outcomes are lacking. The authors examined the impact of overlapping surgery on complication rates in neurosurgical patients. METHODS The authors conducted a retrospective review of consecutive nonemergent neurosurgical procedures performed during the period from May 12, 2014,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 16 publications
(15 reference statements)
4
43
0
Order By: Relevance
“…These data are generally consistent with previous reports. 13,15 A commonly cited concern is that OS may lead to increased anesthesia and operative time for patients, which, in turn, may lead to complications, such as respiratory failure and wound infections. 1,9,10,12,15 Both OS-R and OS-StS cases were significantly longer than NOS cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These data are generally consistent with previous reports. 13,15 A commonly cited concern is that OS may lead to increased anesthesia and operative time for patients, which, in turn, may lead to complications, such as respiratory failure and wound infections. 1,9,10,12,15 Both OS-R and OS-StS cases were significantly longer than NOS cases in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In teaching institutions, overlapping cases are also associated with more resident involvement and graduated autonomy for surgeons in training, which many believe represents an invaluable learning opportunity. 4,9,23 However, recent reports questioning the safety of overlapping surgery have required surgeons and institutions to address this strategy to ensure that the best possible care is being offered to patients. 16,21 Few studies have been performed on this subject to date, and recent changes in practice have been driven by anecdotal reports of surgical complications in overlapping or concurrent cases.…”
Section: Discussionmentioning
confidence: 99%
“…1,21 Concerns about patient safety have led to nationwide changes in surgical scheduling regulations; however, limited data examining this practice exist. No studies published to date have found any evidence of worse outcomes with overlapping surgery; 5,9,11,23 however, these studies examined heterogeneous populations of patients undergoing a variety of neurosurgical procedures.…”
mentioning
confidence: 99%
“…Ultimately, as other authors have noted [3], the safety and effectiveness of overlapping surgeries are undoubtedly variable across procedures and institutions, and further study will be necessary to elucidate when this practice is appropriate. The definition of the “critical portion of the case” is subject to debate.…”
Section: Discussionmentioning
confidence: 99%